Effects of Polymorphisms in the SjSP-13 Gene of Schistosoma japonicum on Its Diagnostic Efficacy and Immunogenicity - Xu, Xindong; Cui, Xiaobing; Zhu, Liufang; Li, Zhengli; Zhang, Yuanbin; Ma, Li; Pan, Weiqing (Frontiers in Microbiology, 2018)
Schistosomiasis japonica is one of the most prevalent parasitic diseases in China. The scarcity of effective diagnostic tools is a major factor that contributes to the high prevalence of schistosomiasis japonica. SjSP-13 is a promising serological diagnostic biomarker of the disease. However, it is unclear whether polymorphisms in SjSP-13 affect its diagnostic efficacy and immunogenicity. Here, we found the SjSP-13 gene was highly polymorphic, and all the alleles of the gene were clustered into two clades, clade A and B. SjSP-13.6 and SjSP-13.25, the representative alleles of clade A and B, were produced in E.coli. The diagnostic value of SjSP-13.6 (AUC = 0.983 ± 0.006), was found to be similar to the SjSP-13.25 (AUC = 0.973 ± 0.009) by receiver operating characteristic (ROC) analysis. SjSP-13.6 and SjSP-13.25 have the same specificity (96.7%), while the sensitivity of SjSP-13.6 (90.4%) is slightly but not significantly higher than SjSP-13.25 (85.2%). The combination use of the two alleles (SjSP-13.6/25) didn’t increase the diagnostic performance of SjSP-13 as the AUC value of SjSP-13.6/25 is 0.977 ± 0.009, lower than individual SjSP-13.6 (AUC = 0.983 ± 0.006). In addition, we found the immunogenicity of clade A alleles is significantly higher than clade B in S. japonicum naturally infected animals and patients, as the mean antibody levels of SjSP-13.6 was significantly higher than SjSP-13.25. We conclude that polymorphisms of the SjSP-13 gene should not affect its diagnostic efficacy, and it is not necessary to combine the alleles of the two clades for diagnosis of schistosomiasis.